Accessibility of Electronic Resources for Students with Disabilities - Penchev Bonimir; Todoranova Latinka (Acta Educationis Generalis)
Introduction: The rapid development of technologies provides more opportunities and ways to adapt the learning environment to the individual needs of students with disabilities.